2022
DOI: 10.1111/jonm.13552
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' disaster core competencies and resilience during the COVID‐19 pandemic: A cross‐sectional study from Turkey

Abstract: Aim:The aim of this study is to determine nurses' disaster core competency levels, compare them based on characteristics and examine the relationships with psychological resilience.Background: Since nurses constitute a critical part in the health care services, it is important to understand the competencies and effective factors in their disaster preparedness. Methods:The data were collected from 489 nurses between January and February 2021 with an introductory information form, the Nurses' Perceptions of Disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
4
4
0
Order By: Relevance
“…The study results indicated no significant difference in the total scores of nurses’ clinical competence before and during the COVID-19 epidemic and nurses received moderate clinical competence in both situations. Ahmadi et al (2022) supported our results and reported nurses’ moderate clinical competence in the COVID-19 wards [ 21 ], but Alan et al (2022) in Turkey found that nurses’ professional competences in the COVID-19 wards were above the average level [ 39 ]. Different results may be due to the different research settings, hospital conditions, nurses’ working conditions in the wards, and managers’ supports from nurses in different dimensions during the epidemic.…”
Section: Discussionsupporting
confidence: 75%
“…The study results indicated no significant difference in the total scores of nurses’ clinical competence before and during the COVID-19 epidemic and nurses received moderate clinical competence in both situations. Ahmadi et al (2022) supported our results and reported nurses’ moderate clinical competence in the COVID-19 wards [ 21 ], but Alan et al (2022) in Turkey found that nurses’ professional competences in the COVID-19 wards were above the average level [ 39 ]. Different results may be due to the different research settings, hospital conditions, nurses’ working conditions in the wards, and managers’ supports from nurses in different dimensions during the epidemic.…”
Section: Discussionsupporting
confidence: 75%
“…(2022) recently reported low to moderate levels of resilience among healthcare workers in United Arab Emirates during the second wave of the COVID‐19 pandemic which is consistent with this study. Our study results also concur with the findings from previous research conducted elsewhere using CD‐RISC 25‐items such as studies conducted in Australia (Guo et al., 2019) and Turkey (Alan et al., 2022).…”
Section: Discussionsupporting
confidence: 92%
“…There is currently a lack of disaster preparedness training for healthcare staff in the United Kingdom. Therefore, considering training that includes professional competencies and psychological preparedness (Alan et al., 2022) would have the benefits in enhancing nurses' capabilities and resilience to respond effectively to future disasters and reduce the risk of burnout. Nurse educators and managers should take a leadership role in developing and planning disaster preparedness training for nurses to enhance their capabilities and resilience in responding to future disasters and reduce the risk of burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that working in a management role fosters resilience because the nurses in these positions have better life-work balance compared to bedside nurses [51]. Furthermore, organizational support [52], disaster experiences [53] and coping with the stressors in nurse managers' roles helps to build resilience [54]. Dealing with competing priorities also has a positive effect on nurse managers' resilience [55].…”
Section: Discussionmentioning
confidence: 99%